Competitive advantage: mediator of managerial competence and financial performance of commercial banks in Uganda - Kamukama, Nixon; Kyomuhangi, Diana S.; Akisimire, Richard; Orobia, Laura A. (African Journal of Economic and Management Studies, 2017)
This paper examines the mediating role of competitive advantage in the relationship between managerial competence and financial performance of commercial banks in Uganda. Design/methodology/approach – A cross-sectional survey was employed using 22 fully licensed and operational commercial banks in Uganda. Data were analyzed using descriptive statistics, zero order correlation, and hierarchical regression analyses. Further, the bootstrap method was used to test the mediation effect of competitive advantage. All the analyses were performed using SPSS v21. Findings – The findings reinforce the important position of managerial competence on financial performance of commercial banks. First, managerial competence enhances firms’ competitive advantage. Second, managerial competence has an indirect effect on financial performance through competitive advantage. Overall, managerial competence and competitive advantage are strong predictors of financial performance of commercial banks. Research limitations/implications – The study employed only a single research methodological approach, therefore future research could be undertaken using a mixed approach and triangulate to compare findings. Furthermore, the findings from the present study are cross-sectional, considering the limitations there in, a longitudinal approach should be explored.
Keywords: Managerial competence; Competitive advantage; Financial performance